Development of Arabic Language Curriculum With Integration-Interconnection Paradigm Referring KKNI and SN-DIKTI - Muhammad Hattab; Munirul Abidin (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This research is a library research study aimed at examining the development of an Arabic language education curriculum with an integration-interconnection paradigm referring to KKNI and SN-DIKTI with several problem formulations, namely, (1) What is the profile of the curriculum referring to KKNI and SN-DIKTI with an interconnection integration paradigm in the Language Education Masters program Arabic (PBA) UIN Maulana Malik Ibrahim Malang, (2) Has the curriculum structure been prepared based on the needs of students who will face challenges in society as the goals formulated by the KKNI? Methods of data analysis using descriptive-analytical. This study's result is that the curriculum profile refers to KKNI and SN-DIKTI with the paradigm of interconnection integration. The curriculum structure that has been prepared according to the objectives formulated by the KKNI is grouped into introductory competency courses, methodology competency courses, general competency courses and supporting competency courses with a total of 53 credits.